Effects of Dietary Resveratrol, Bile Acids, Allicin, Betaine, and Inositol on Recovering the Lipid Metabolism Disorder in the Liver of Rare Minnow Gobiocypris rarus Caused by Bisphenol A - Yingying Zhang; Yinan Jiang; Ziying Wang; Jiayu Wang; Mingzhen Zhu; Hui Yang (Aquaculture Nutrition)
The fatty liver is one of the main problems in aquaculture. In addition to the nutritional factors, endocrine disrupter chemicals (EDCs) are one of the causes of fatty liver in fish. Bisphenol A (BPA) is a plasticizer widely used in the production of various plastic products and exhibits certain endocrine estrogen effects. Our previous study found that BPA could increase the accumulation of triglyceride (TG) in fish liver by disturbing the expression of lipid metabolism-related genes. How to recover the lipid metabolism disorder caused by BPA and other environmental estrogens remains to be explored. In the present study, Gobiocypris rarus was used as a research model, and 0.01% resveratrol, 0.05% bile acid, 0.01% allicin, 0.1% betaine, and 0.01% inositol were added to the feed of the G. rarus that exposed to 15 μg/L BPA. At the same time, a BPA exposure group without feed additives (BPA group) and a blank group with neither BPA exposure nor feed additives (Con group) were setted. The liver morphology, hepatosomatic index (HSI), hepatic lipid deposition, TG level, and expression of lipid metabolism-related genes were analyzed after 5 weeks of feeding. The HSI in bile acid and allicin groups was significantly lower than that in Con group. The TG in resveratrol, bile acid, allicin, and inositol groups returned to Con level. Principal component analysis of TG synthesis, decomposition, and transport related genes showed that dietary bile acid and inositol supplementation had the best effect on the recovery of BPA-induced lipid metabolism disorder, followed by allicin and resveratrol. In terms of lipid metabolism-related enzyme activity, bile acid and inositol were the most effective in recovering BPA-induced lipid metabolism disorders. The addition of these additives had a restorative effect on the antioxidant capacity of G. rarus livers, but bile acids and inositol were relatively the most effective. The results of the present study demonstrated that under the present dosage, bile acids and inositol had the best improvement effect on the fatty liver of G. rarus caused by BPA. The present study will provide important reference for solving the problem of fatty liver caused by environmental estrogen in aquaculture.